GMR array uniform eddy current probe for defect detection in conductive specimens - Postolache, O. (2014)
In this work an optimized uniform eddy current probe architecture including two planar excitation coils, a rectangular magnetic field biasing coil and a GMR magnetometer sensor array is presented. An ac current is applied to the planar spiral rectangular coil of the probe, while a set of GMR magnetometer sensors detects the induced magnetic field in the specimens under test. The rectangular coil provides the DC uniform magnetic field, assuring appropriate biasing of the GMR magnetometers of the probe, setting-up the functioning point on the linear region and at the same branch of the GMR static characteristics. The differences on the images obtained for the same specimen for each GMR are reduced if all sensors are biased on the same working point. Elements of the automated measurement system used to inspect the plate under test using the proposed eddy current probe, including a validation procedure based on a 2D template matching algorithm and the corresponding experimental results are included in the paper